2018
DOI: 10.18203/2394-6040.ijcmph20184006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutrition education intervention on undernutrition among under five children in urban and rural areas of Bhopal district, Madhya Pradesh

Abstract: Background: Nutrition education is defined as instruction or training intended to lead to acquired nutrition-related knowledge and/or nutrition-related skills and be provided in individual. It is also demonstrably capable of improving dietary behaviour and nutrition status on its own.Methods: A prospective observational study was conducted in the urban and rural ICDS projects of Bhopal district, Madhya Pradesh from July 2014 to June 2015. Three types of instruments were used: NIPCCD Suposhan Guide, a structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…The current study is also consistent with the Alexandria study, which found a decrease in the percentage of underweight, stunted, and wasted people [ 29 ]. The nutrition intervention conducted in Bhopal district, Madhya Pradesh showed a percentage reduction in underweight among children after intervention [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current study is also consistent with the Alexandria study, which found a decrease in the percentage of underweight, stunted, and wasted people [ 29 ]. The nutrition intervention conducted in Bhopal district, Madhya Pradesh showed a percentage reduction in underweight among children after intervention [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The need for development of intervention in order to build capacity of mothers/primary caregivers has been emphasized in previous studies. (19)(20)(21)(22)…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire developed to assess knowledge mothers consisted 28 multiple choice questions in following areas: malnutrition, minor deficiency diseases and nutrition rich diet, feeding and importance, complementary feeds, management, prevention and complications and utilization of health services. Total score of tools was 28 which was categorized into good (above 20), average (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and poor (below 10). The tool used to assess the nutrition related practices of mothers was structured five-point Likert scale.…”
Section: Methodsmentioning
confidence: 99%
“…Selain itu memiliki efek jangka panjang pada perilaku pemberian makan orang tua berdampak pada kesehatan anak-anak mereka. (Meena and Meena, 2018) Menyusun menu seimbang dengan cara pada setiap menu hidangan harus mengandung kalori dari karbohidrat, protein, lemak, di sempurnakan dengan vitamin dan mineral. Penyusunan menu balita yang baik dengan cara: memilih makanan yang cukup mengandung kalsium dan zat besi Menu makanan balita ditentukan sesuai dengan pertumbuhan anak, kemampuan menerima rangsangan makan dan mencerna makanan.…”
Section: Pembahasanunclassified